Control strategy of a fuel-cell power module for electric forklift. (19th October 2021) - Radica, Gojmir; Tolj, Ivan; Markota, Dario; Lototskyy, Mykhaylo V.; Pasupathi, Sivakumar; Yartys, Volodymyr
Abstract: Fuel cell-battery hybrid systems for the powertrain, which have the advantage of emission-free power generation and adapt to material transport and emission reduction, are investigated. Based on the characteristics of the fuel cell system and the characteristics of the electric forklift truck powertrain system, this work defines the design principle of the control strategy to improve overall performance and economy. A simulation platform for fuel cell and electric vehicles has been established. The optimal performance of the fuel cell stack and the battery capacity were defined for the specific application. An energy control strategy was defined for different operating cycles and operating conditions. Model validation involved comparing simulation results with experimental data obtained during VDI60 test protocol. The main parameters that influence the forklift performance were defined and evaluated, such as energy loss, fuel cell operating conditions and different battery charging cycles. The optimal size of the fuel cell stack of 11 kW and the battery of 10 Ah was determined for the specific load profile with the proposed control strategy. The results obtained in this work forms the basis for an in-depth study of the energy management of fuel cell battery drive trains for forklift trucks. Highlights: Lift truck simulation model with hybrid power pack is developed. PEMFC-Battery hybrid model for lift truck application was analyzed. Real lift truck load cycle was simulated. Balance of plant optimization and control strategy was done.